2008
DOI: 10.1016/j.chemolab.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties and error propagation in kinetic hard-modelling of spectroscopic data

Abstract: A novel method is presented for the rigorous propagation of uncertainties in initial concentrations and in dosing rates into the errors in the rate constants fitted by multivariate kinetic hard-modelling of spectroscopic data using the Newton-Gauss-Levenberg/Marquardt optimisation algorithm. The method was successfully validated by Monte-Carlo sampling. The impact of the uncertainties in initial concentrations and in the dosing rate was quantified for simulated spectroscopic data based on a second and a formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Note that for all experimental conditions (a to e), quick injections were done within 24 s. Experimental conditions (a) are similar to those used in previous papers [21,22]. The experiment performed under these conditions (Experiment #1) was analysed assuming batch and semibatch conditions.…”
Section: Experimental Conditions (A)-dosing Aamentioning
confidence: 98%
See 3 more Smart Citations
“…Note that for all experimental conditions (a to e), quick injections were done within 24 s. Experimental conditions (a) are similar to those used in previous papers [21,22]. The experiment performed under these conditions (Experiment #1) was analysed assuming batch and semibatch conditions.…”
Section: Experimental Conditions (A)-dosing Aamentioning
confidence: 98%
“…Products of the reaction are benzophenonephenylhydrazone (BP), water and the regenerated catalyst (Aa). This model reaction has been extensively described for acetic acid being dosed into benzophenone and phenylhydrazine [21,22]. In a recent paper, we have also shown that this condensation reaction and the optimisation of its rate constant are highly reproducible [21], thus being an ideal case study to validate our systematic method to treat kinetic rank deficiencies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the decoupling of the various rates and extents, each reaction and each mass transfer can be dealt with individually, unlike in the simultaneous identification, where an overall model including all the reactions and mass transfers has to be postulated [4][5][6]. Hence, the reaction and masstransfer rate parameters estimated by the incremental methods are largely uncorrelated.…”
Section: List Of Symbolsmentioning
confidence: 99%